2020
DOI: 10.2174/1386207323666200219123214
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Combinatory Antifungal Activities of Ammoides verticillata, Allium sativum and Curcuma longa Essential Oils Against Four Fungi Responsible for Tomato Diseases

Abstract: Background: Tomato is considered a model plant in genetics and is one of the most economically important crops of all those that exist in the world. Several species of fungi are reported on tomato fruit, causing damage both during cultivation and after harvest. Some of the appropriate actions that could be initiated to resolve the problem are to develop and search for new antimicrobial substances isolated from the bioactive natural products, such as essential oils. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…On the other hand, the essential oil obtained from other parts of C. longa with different chemical compositions has also shown antimicrobial activity. In this sense, C. longa essential oil dominated by oxygenated monoterpenes (82.0%) displayed promising in vivo antifungal activity against P. expansum and Rhizopus stolonifer when combined with A. sativum essential oil, representing a natural alternative to chemical fungicides in tomato protection [216]. Similarly, C. longa essential oil rich in monoterpenes (20.4% α-phellandrene, 10.3% 1,8-cineole and 6.19% terpinolene) and with considerable quantities of αand βturmerone (19.8% and 7.35%) presented one of the highest MICs (0.06-0.36 mg/mL) with respect to 11 different essential oils against five food-spoilage yeasts [217] (Table 3).…”
Section: Prevention and Inhibition Of Microbial Attack In Crops And Food-spoilage Microorganismsmentioning
confidence: 99%
“…On the other hand, the essential oil obtained from other parts of C. longa with different chemical compositions has also shown antimicrobial activity. In this sense, C. longa essential oil dominated by oxygenated monoterpenes (82.0%) displayed promising in vivo antifungal activity against P. expansum and Rhizopus stolonifer when combined with A. sativum essential oil, representing a natural alternative to chemical fungicides in tomato protection [216]. Similarly, C. longa essential oil rich in monoterpenes (20.4% α-phellandrene, 10.3% 1,8-cineole and 6.19% terpinolene) and with considerable quantities of αand βturmerone (19.8% and 7.35%) presented one of the highest MICs (0.06-0.36 mg/mL) with respect to 11 different essential oils against five food-spoilage yeasts [217] (Table 3).…”
Section: Prevention and Inhibition Of Microbial Attack In Crops And Food-spoilage Microorganismsmentioning
confidence: 99%
“…The results clearly showed that garlic EO has an inhibitory efficacy against two wood decay fungi ( Table 1 ). Similarly, the garlic EO was demonstrated to possess antifungal activity against the agents of anthracnose in avocado, Colletotrichum gloeosporioides [ 44 ]; of tomato diseases, Penicillium expansum and Rhizopus stolonifer [ 45 ]; Aspergillus parasiticus , A. niger [ 46 ] and A. terreus [ 47 ]; Fusarium oxysporum [ 48 ] and F. thapsinum [ 47 ]; of grapes post-harvest disease, Botrytis cinerea [ 49 ]; Penicillium citrinum [ 50 ] and P. funiculosum [ 47 ]. In addition, in the previous reports, garlic EO or extract exhibits insecticidal, antifeedant, and repellent activities against many insects and mites [ 15 , 28 , 29 , 38 , 43 ].…”
Section: Discussionmentioning
confidence: 99%